Interaction among a child with developmental disabilities and peers in a regular early education center - Maria Clara de Freitas; Enicéia Gonçalves Mendes (Universidade Federal de Santa Maria (UFSM), 2009)
As a part of a larger project, this research aimed to describe and analyze the situation of children with special needs in Early Education Centers, most specifically the interaction among children. As procedure videotaped free-play activities were categorized to describe the interactive behavior of children in relation to each other (in pairs) on: frequency, direction, duration, topography, and the status of the child, which could be considered isolated, grouped and in teracting, only grouped or alone. These data were analyzed in interactive dyads in order to compare the quality of interaction when the disabled child was present or not. The results indicated that the situation examined had strongly positive aspects, such as the high frequency of interaction, even if to the adults. However, she did spent great time alone, and their interactions with peers were smaller and of different quality (basically less verbal) compared to the interaction among the other children. Thus, based on the belief that social inclusion would be achieved only when typically developed children kept the same quality of relationships with children with and without developmental delays, the general conclusion indicated little success in the analyzed situation. Possibilities of intervention to promote interaction between children are discussed.